EXPLORING OF THE IMPACT OF CAPITAL MARKET LITERACY AS A MODERATOR ON INVESTORS’ REINVESTMENT INTENTION IN THE INDONESIAN STOCK MARKET - Thasrif Murhadi; Aida Fitri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to explore the influence of capital market literacy as a moderating variable on the relationship between Expertise, Reputation, and Investor Trust with the investors reinvestment intention in the Indonesian stock market. Data were collected from 454 respondents using a questionnaire distributed to stock investors across Indonesia. The study employed a non-probability sampling approach with the purposive sampling method. Data analysis was conducted using descriptive and verificative analysis techniques, employing the Structural Equation Modelling (SEM) AMOS as the analytical tool. The research results indicate that expertise and reputation have a significant direct impact on Investor Trust. However, expertise and reputation do not have a direct influence on reinvestment intention. Additionally, investor trust has been proven to be a significant mediator in the relationship between expertise and reputation with reinvestment intention. The most intriguing finding is that capital market literacy, as a moderating variable, can moderate the relationship between investor trust and reinvestment intention. This suggests that the level of capital market literacy can strengthen the influence of investor trust on the reinvestment intention. The results of this research provide a deeper understanding of the role of capital market literacy in shaping the reinvestment decisions of investors in the Indonesian stock market, as well as its implications for investment practices and the development of capital market literacy in the future.